Simulasi Sistem Antrian Pelayanan Take Away di Gerai Minuman Teh - Putu Wahyou Widiadnyana; I Putu Reno Swambara Lingga; Ahmad Maulana; Chanysia Feychin Romani; Ni Luh Putu Lilis Sinta Setiawati (Program Studi Teknik Industri Universitas Setia Budi, 2025)
An efficient queuing system plays a crucial role in improving service quality and customer satisfaction. Inefficiencies in the queuing system of food and beverage businesses can lead to long lines and decreased customer satisfaction due to prolonged waiting times for ordering. Therefore, addressing queue inefficiencies requires improvements in queuing rules, facilities, or resources. This study investigates inefficiencies in the take-away service queuing system at a tea beverage outlet in a shopping mall in Bali, which results in long waiting times and customer dissatisfaction, especially during peak hours. The objective of this research is to analyze the existing queuing system, identify key bottlenecks, and propose improvements to enhance service efficiency. The method used is system simulation with ProModel, where data is collected through direct observation and time measurements at various service stages. The simulation results indicate that the bottleneck occurs at the cashier counter, causing the average customer waiting time to reach 1,855 seconds. The outlet is only able to serve 71.2% of the total potential customers within three hours. Adding one more cashier counter successfully increased the number of customers served from 88 to 156 within three hours, reduced the average waiting time to 1,340 seconds, and improved processing capacity to 95.31%. In conclusion, the proposed improvements in this study can significantly enhance the efficiency of the queuing system and customer satisfaction at the tea beverage outlet.